Excellence in Research:A Hybrid Transtibial Technique Combines the Strengths of theAnteromedial Portal and Transtibial Approaches: A Prospective Randomized Controlled Trial. Issue 7 (31st July 2020) - Saltzman, Bryan; Corpus, Keith; Connor, Patrick; Fleischli, James; Trofa, Dana; David, Piasecki
Objectives: Improved biomechanical and clinical outcomes have been reported when femoral anterior cruciate ligament (ACL) tunnels are centered on the native footprint. The anteromedial (AM) portal technique achieves improved aperture position when compared to a transtibial (TT) approach but sacrifices technical ease and creates a shorter more acutely angulated tunnel. A hybrid transtibial technique (HTT) technique using medial portal guidance of a flexible transtibial guide wire without the need for knee hyperflexion may combine the strengths of both the AM and TT approaches. The authors hypothesized that this HTT technique would achieve anatomic femoral tunnel apertures similar to the AM technique, but with longer and less angulated femoral tunnels similar to a TT technique. Methods: A prospective randomized controlled trial was implemented where 30 consecutive patients with acute, primary ACL tears were randomized to receive a TT, AM or HTT technique for their reconstruction. A total of 46 patients were assessed for eligibility in the investigation (Figure 1). All patients underwent 3D CT scans of the operative knee 6 weeks postoperatively to characterize tunnel positions. Femoral and tibial tunnel aperture positions and tunnel lengths, as well as the graft bending angle in the sagittal and coronal plane were measured. Results: There were no significant differences between the patient demographics of the three groups. Tibial tunnel lengths and aperture positions were identical between the three groups. The AM portal and HTT techniques achieved identical femoral aperture positions in regards to both height (p=0.75) and depth (p=0.72). On the other hand, compared to the AM portal and HTT techniques, respectively, femoral apertures created by the TT technique were significantly higher (p<0.001 and p<0.001) and shallower (p=0.001 and p<0.001) in the notch. The average femoral tunnel lengths varied significantly between the three groups measuring 35.16 mm, 41.64 mm, and 54.13 mm for the AM, HTT and TT groups, respectively (p<0.001). Lastly, there were no differences between the average coronal (164.0 degrees versus 158.8 degrees, p=0.190) and sagittal (114.0 degrees versus 111.0 degrees, p=0.358) graft bending angles between the TT and HTT groups, respectively. By contrast, compared to the TT and HTT groups, respectively, the graft bending angles created with an AM technique were significantly more acutely angled in the coronal (146.3 degrees, p<0.001, p<0.006) and sagittal (100.5 degrees, p=0.014, p=0.013) planes. Conclusion: The HTT technique achieves femoral aperture positions equally as anatomic as an AM portal technique, but with longer and less acutely oriented grafts similar to a transtibial approach. These advantages will decrease the incidence of graft tunnel mismatch as well as reduce the amount of stress imparted onto the graft by avoiding an acute graft bending angle. As such, this hybrid approach may represent a beneficial combination of both transtibial and AM portal techniques.